2010
DOI: 10.1177/1756283x10387203
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of irritable bowel syndrome: beyond fiber and antispasmodic agents

Abstract: Irritable bowel syndrome (IBS) is a chronic functional disorder of the gastrointestinal tract of unknown etiology. The diagnosis of IBS is made clinically, using symptom-based criteria such as the Manning or Rome criteria. Medical therapy for this condition has traditionally been directed towards symptom relief, using fiber or antispasmodic agents. In recent years, emerging data have confirmed the efficacy of antidepressants, psychological therapies, 5-HT 3 antagonists, 5-HT 4 agonists, and probiotics in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 114 publications
1
18
0
1
Order By: Relevance
“…IBS is a prevalent chronic relapsing condition that is regularly associated with significant disability and has a considerable financial burden for the health service due to the consumption of resources including physician time, investigations, and costs of treatment [66] . The presence of clinically significant psychiatric symptoms in patients with IBS is an indication for psychotherapy, especially CBT.…”
Section: Resultsmentioning
confidence: 99%
“…IBS is a prevalent chronic relapsing condition that is regularly associated with significant disability and has a considerable financial burden for the health service due to the consumption of resources including physician time, investigations, and costs of treatment [66] . The presence of clinically significant psychiatric symptoms in patients with IBS is an indication for psychotherapy, especially CBT.…”
Section: Resultsmentioning
confidence: 99%
“…(27) At present, no drug has been shown to alter the clinical course of IBS, and most of the treatments available currently have only a modest effect on symptom improvement, with their effi cacy in the longer term remaining unknown. (28) By contrast, acupuncture and Mox can effectively treat IBS through regulation of brain, gastrointestinal tract and other channels. (14)(15)(16)(17)(18)(19)(20)29) In this trial, we observed that 5-HT and 5-HT3R expressions in colon tissue of D-IBS patients before treatment were higher than healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…59, 61, 71 Since SSRIs tend to stimulate gut motility, they may be more useful in patients with IBS-C. 66, 68, 71 The adverse effects of SSRIs include diarrhea, nausea, and cramping. 81 Global symptoms of IBS are more likely to improve with the use of antidepressants, although there are limited data on their safety and tolerability within this treatment context.…”
Section: Pharmacologic Treatments For Ibs Symptomsmentioning
confidence: 99%